Caracterização do genoma cloroplastidial de Caryocar cuneatum (Caryocaraceae) - Mendes, Millena Silva (2023)
The Caryocaraceae family (1845) belongs to the order Malpighiales, which has 36 families, 716 genera and 16,065 species. Caryocaraceae consists of two genera Anthodiscus G. Mey. with ten species and Caryocar L. with 16 species. The present work aims to carry out the de novo assembly of the chloroplastidial genome of Caryocar cuneatum Wittm. and to carry out comparative analyzes regarding the structure and composition of the genome with other species of Malpighiales. For this, the total DNA of an individual of C. cuneatum was sequenced using the MiSeq platform (Illumina), paired-end (2x300) with the MiSeq V3 600 cycles kit. The plastome was assembled using the NOVOPlasty v3.2 program and annotated using the CHLOROBOX. For comparative analyses, chloroplast genomes of 8 species belonging to the Malpighiales order (Caryocar brasiliense, Caryocar glabrum, Lophopyxis maingayi, Drypetes indica, Aspidopterys concava, Byrsonima crassifolia, Balanops balansae, Couepia ovalifolia) were used. The chloroplast genome of C. cuneatum had a size of 165,767 bp, composed of a single copy major region of 83,968 bp, a single copy minor region of 11,854 bp, separated by two inverted repeat regions of 34,973 bp. It has 131 genes, 90 protein coding, 33 transfer RNAs and 8 ribosomal RNAs. The rpl32 gene is not present in species in C. cuneatum and in the other two species of Caryocar. The size of the plastid genome of the genus Caryocar presents itself a lot. For the other species, there was variation in size, structure and genomic composition. The InfA gene is pseudogenized in all analyzed species and was not found in A. concava. In the analysis of synonymous and non-synonymous mutations, the rpl20 gene is under neutrality and the other genes are under negative selection. For the nucleotide diversity in Caryocar genomes, it was possible to identify two hotspot regions: trnS-GCU - trnG-UCC and rbcL - atpB, which can be used as possible molecular markers for DNA barcoding. The phylogenetic tree obtained good support values for nodes in Caryocaraceae, validating the systematic position of C. cuneatum within the family and evidence of its relationship with its sister groups C. brasilense and C. glabrum. In conclusion, this study provides the first genome of C. cuneatum sequenced, information on genomic characterization and the knowledge provided here can be used for further studies and technological.